Production of biodiesel using blend of waste cooking oil in different concentration with kerosene. (2022) - Soni, Shubham; Banodiya, Kartik; Agrawal, Krishnanshu; Singh, Prashant; Thakur, Manish
Abstract: The objective of the presented work is to produce bio-diesel, by mixing used cooking oil in different concentrations with kerosene, and to test the chemical properties of the bio-diesel samples. In this study, the samples of Sunflower Oil, Peanut Oil, and Soybean Oil are collected and mixed in different concentrations with kerosene to produce different samples of biodiesel. The Flashpoint and Fire point of these samples are calculated using Cleveland's open cup set up. In the performed experiment it is observed that the highest flashpoint is obtained for Sunflower Oil-based biodiesel and the least for Peanut-based biodiesel when the oil samples and kerosene is mixed in a 1:1 ratio. For the same mixing ratio, the fire point of Sun flower oil-based biodiesel and Soybean oil-based biodiesel has the highest value, whereas Peanut oil-based biodiesel has the least value.